Exploring the Role of Gratitude in Various Psychological Paradigms - Prabawa, Abi Fa’izzarahman; Hidayah, Nur; Indreswari, Henny; Atmoko, Adi; Hotifah, Yuliati; Antika, Eni Rindi; Mahalle, Salwa (COUNS-EDU: The International Journal of Counseling and Education, 2025)
This study conducts a systematic literature review of gratitude-based interventions from 2020 to 2025 to assess their psychological impact and position them within the therapy paradigms of Rocco Cottone. Based on 52 peer-reviewed articles identifying through a PRISMA-guided search, the results show that gratitude interventions effectively reduce the symptoms of depression, anxiety, stress, and trauma-related distress. These functions improve Emotional and Spiritual Well-being, self-regulation, and relationships across various populations including students, employees, patients, and caregivers. A major uniqueness of this review is the application of Cottone's paradigmatic pie—psychological internal, external, inter, cross, and multi paradigms—contributing an innovative angle to analyzing the mechanisms and contexts of gratitude interventions. Most of the interventions were found within inter and internal paradigm models, whereas the transparadigm model which integrates biological, psychological, and social aspects, showed particular promise in clinical and organizational settings. This review also highlights the underappreciated role of gratitude in responding to post-digital socio-psychological stress uniquely relevant in today's fractured world. The study concludes that gratitude is a strategically valuable, multifaceted, flexible, and low-cost resource that can be easily weaved into modern counseling practice. Discussion is provided on implications for theory, practice, and future inquiries.